Tongkat Tunanetra Menggunakan Sensor Ultrasonik dan GPS Berbasis Mikrokontroler - Gunawan, Fikri; Roza, Indra; Siregar, Lisa Adriana (Universitas Harapan Medan, 2025)
Conventional blind canes have limitations in providing accurate information about the user's environmental conditions, especially in recognizing obstacles and determining location. Therefore, this study aims to design and build a smart blind cane equipped with ultrasonic sensors and a microcontroller-based GPS system. This cane is designed to help blind users detect obstacles around them and determine their location more independently. The main system of this cane consists of an ultrasonic sensor to detect the distance of obstacles in front of the user and a GPS module to track the user's location. Data from the sensors and GPS are processed by a microcontroller, which then provides feedback to the user through vibrations and sounds. When an obstacle is detected within a certain distance, vibrations will be activated to provide a warning, while location information can be accessed through an application or other supporting devices. The test results show that this blind cane has a high level of accuracy in detecting obstacles up to a distance of 2 meters and fairly good positioning accuracy with an integrated GPS system. This cane can improve the mobility and sense of security of users in different environments. Thus, this design makes a positive contribution to assistive technology for the blind, enabling them to be more independent in their daily activities.